Uso de material didáctico y su incidencia en el desarrollo cognitivo de los estudiantes del tercer año de educación básica de la unidad educativa “rosa Chávez Sellan” de la parroquia Mata de cacao de la provincia de los ríos, periodo 2015-2016 - Carbo Velarde, Marcia Elizabeth (2015)
In this present final report, I aimed to design a learning guide to encourage the use of teaching materials to develop the cognitive area of the students of the year of the Rosa Chávez Sellan educational unit, Mata de Cacao parish, Los Ríos Province. The development of this Research is aimed at determining if teachers apply didactic strategies if they use appropriate teaching materials so that children develop the cognitive area without any problem is why the teacher should plan and implement everything he teaches. Once you put everything into practice the student will be made to be creative, imaginative, productive, understanding and able to develop their skills and dexterity in an indisputable way. This research is done in order for the teacher to help his students to enhance and increase the intellectual capacities of children. In this research, teachers, parents and students were surveyed to verify if teachers are applying the learning strategies and confirm if students know how to use the teaching materials correctly. As a solution to different problems encountered, a strategy guide will be developed that will involve both the teacher and the parents to help third-year students in the above-mentioned educational unit develop cognitive skills.